Harsh Parenting and Adolescent Health: A Longitudinal Analysis with Genetic Moderation - Brody, Gene H. (Health Psychol, 2013)
OBJECTIVE: This study was designed to examine the prospective relations of harsh parenting during preadolescence, anger across adolescence, and a health phenotype at late adolescence among African American youths living in the rural South. A second purpose was to determine whether, for genetic reasons, some youths will be more sensitive than others to a harsh parenting to anger to poor health pathway. METHODS: Participants were 368 youths (age 11.2 at the first assessment) who provided data on receipt of harsh parenting during preadolescence (ages 11 to 13), anger across adolescence (ages 16 to 18), and a health phenotype consisting of C Reactive Protein, depressive symptoms, and health problems at age 19. Youths were genotyped at the 5-HTTLPR at age 16. RESULTS: The data analysis revealed that (a) harsher parenting was associated positively across time with anger and poor health, (b) anger across adolescence also was associated positively across time with poor health, (c) anger served as a mediator connecting harsh parenting and poor health, and (d) the harsh parenting to anger to poor health pathway was significant only for youths carrying one or two copies of a short allele at the 5-HTTLPR. CONCLUSIONS: These findings are consistent with the hypothesis that harsh parent-child interactions presage health through effects on emotion regulation, particularly anger. This mediational pathway pertained only to youths carrying a gene that confers sensitivity and reactivity to harsh family processes and the negative emotional states they occasion.